2017
DOI: 10.1002/mbo3.514
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into the pathogenicity and environmental adaptability of Enterococcus hirae R17 isolated from pork offered for retail sale

Abstract: Genetic information about Enterococcus hirae is limited, a feature that has compromised our understanding of these clinically challenging bacteria. In this study, comparative analysis was performed of E. hirae R17, a daptomycin‐resistant strain isolated from pork purchased from a retail market in Beijing, China, and three other enterococcal genomes (Enterococcus faecium DO, Enterococcus faecalis V583, and E. hirae ATCC ™9790). Some 1,412 genes were identified that represented the core genome together with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 85 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…The genes are annotated as PBP2b, PBP1b, PBP1a, and PBP2x, and have a low identity with PBP5 according to BLASTP. Despite the presence of these PBPs, however, E. durans KLDS6.0930 is sensitive to penicillin and ampicillin, a phenomenon also observed in E. hirae R17 (Peng et al, 2017). …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The genes are annotated as PBP2b, PBP1b, PBP1a, and PBP2x, and have a low identity with PBP5 according to BLASTP. Despite the presence of these PBPs, however, E. durans KLDS6.0930 is sensitive to penicillin and ampicillin, a phenomenon also observed in E. hirae R17 (Peng et al, 2017). …”
Section: Discussionmentioning
confidence: 94%
“…Concerns about the use of enterococci as a double-edged sword have led to an increasing number of studies intended to evaluate the safety of certain enterococci strains (Kopit et al, 2014; Zhang et al, 2016; Peng et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…This means a transdisciplinary approach across the humananimal-environment continuum in order to better understand the problem of AMR in enterococci (97). While enterococcal species other than E. faecium and E. faecalis were discussed in a few studies, in general, there were relatively few studies using a One-Health approach to compare animal, environmental (e.g., water and soil), and human samples (9,11,13,(39)(40)(41)(68)(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
“…As AMR pathogens have emerged, the use of antimicrobials for prophylaxis and metaphylaxis in food producing animals has come under scrutiny for its potential to apply a selective pressure that contributes to the dissemination of AMR and MDR enterococci ( 7 , 11 ). Perhaps the most classic example is in poultry and swine where the previous use of a vancomycin-related glycopeptide, avoparcin, as a growth promoter was associated with carriage of vancomycin-resistant E. faecium (VREfm) in treated herds or flocks through cross-resistance ( 7 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The raw sequence reads were quality trimmed using Trimmomatic ( Bolger et al, 2014 ), sequences with a Phred score less than 25 were removed. To obtain an initial estimate of sequencing coverage of E. lacertideformus present in each library, the trimmed reads were mapped against the Enterococcus hirae strain R17 genome (NCBI GenBank accession CP015516 ) ( Peng et al, 2017 ) using the Burrow-Wheeler Aligner (BWA-MEM v0.7.12) with default settings ( Li and Durbin, 2009 ). This revealed that sample 10702.133 contained the highest coverage depth (mean 1006.52×) in comparison to samples 10706.1 and 10706.10, with mean coverages of 245.72× and 8.73×, respectively.…”
Section: Methodsmentioning
confidence: 99%